DESAIN SET CATUR UNTUK ANAK-ANAK DENGAN MOTIF BATIK KALIMANTAN TIMUR - Andi Farid Hidayanto; Muhammad Wahyudi (Indonesian Society of Applied Science, 2018)
ABSTRACT The design and development of chess set products into a part of the development of design in the business world, especially children's games. But the current chess sets are less varied. Generally chess set that there is only a royal and has a black and white color without any introduction of Indonesian culture, especially batik East Kalimantan. The current chess set also rarely has good storage so chess storage is not neatly arranged when the game is over. With this in mind, a designer tries to create a better item with new innovations. Like designing a chess set that is easily understood by children, designing a chess set that can introduce East Kalimantan batik culture especially Dayak Kenyah batik, and designing chess sets that have aesthetic value. In this report with the title